2017
DOI: 10.1007/s40974-017-0058-7
|View full text |Cite
|
Sign up to set email alerts
|

Energetics, GHG emissions and economics in nitrogen management practices under potato cultivation: a farm-level study

Abstract: The multifarious relationships between nitrogen application, energy consumption and GHG emissions are still not well understood in irrigated potato production system. There is a need to ensure that N and energy use are closely considered to provide useful options for adaptation and to build resilience at the farm level. A field experiment was conducted during the winter (November-March) of 2012-2013 and 2013-2014 at the District Seed Farm, Adisaptagram, Hooghly, West Bengal, India (23°26 0 N latitude and 88°2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
3
2
Order By: Relevance
“…However, our study contradicts the previous findings of Banerjee et al [33] and Ray et al [22] who observed higher energy and cost involvement in potato cultivation. The reason may be that unlike other parts of West Bengal where potato is sown after heavy tillage to pulverize the post-paddy soil, the coastal area is mostly dominated by zero-tillage potato cultivated areas.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our study contradicts the previous findings of Banerjee et al [33] and Ray et al [22] who observed higher energy and cost involvement in potato cultivation. The reason may be that unlike other parts of West Bengal where potato is sown after heavy tillage to pulverize the post-paddy soil, the coastal area is mostly dominated by zero-tillage potato cultivated areas.…”
Section: Discussioncontrasting
confidence: 99%
“…However, such issues do not necessarily imply that agriculture is at a point of no return. In fact, farm-based enterprises still form the main livelihood option for the rural people in Sundarbans [33,34], and they ask for efficient utilization of scarce resources to extract more output from existing production systems. Rainy (kharif ) rice is central to the cropping systems in coastal West Bengal, grown in an estimated area of 3.33 lakh ha with a production of 8.15 lakh tonnes in the South 24 Parganas district [35].…”
Section: Introductionmentioning
confidence: 99%
“…However, our study contradicts previous findings of Banerjee, et al [17] and Ray, et al [29] who observed higher energy and cost involvement in potato cultivation. The reason may be that unlike other parts of West Bengal where potato is sown after heavy tillage to pulverize the post-paddy soil, coastal area is mostly dominated by zero tillage potato cultivated areas.…”
Section: Discussioncontrasting
confidence: 95%
“…However, such propositions do not necessarily imply agriculture's point of no returns in this area. In fact, farm-based enterprises still form the main livelihood option for the rural people in Sundarbans [17,18] and asks for an efficient utilization of scarce resources to extract more output from existing production systems. Rainy (kharif) rice is central to the cropping systems in coastal West Bengal, grown in an estimated area of 3.33 lakh ha with a production of8.15lakh tonnes in south 24 Parganas district [19].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, nitrogen use efficiency (NUE) could not exceed 50% in lowland rice fields in India ( Li et al, 2017 ). The residual N is either lost through surface runoff, leaching, deep percolation or contributes a significant amount of N 2 O (nitrous oxide, a potential greenhouse gas) into the atmosphere ( Banerjee, Sarkar & Ray, 2017 ; Banerjee et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%